alpha-Fetoprotein and albumin genes are in tandem in the mouse genome. - Ingram, R S (1981)
The urine alpha-fetoprotein (AFP) and serum albumin genes most probably arose in evolution as the consequence of a duplication of a common ancestral gene. They have both been previously mapped to chromosome 5 in the mouse. We now have evidence that these genes are closely linked. By using a unique copy DNA probe derived from previously cloned AFP 5' flanking DNA, a recombinant DNA phage has been isolated, from a bacteriophage DNA library, that contains sequences flanking the 5' end of the AFP gene and the 3' end of the albumin gene. Restriction endonuclease mapping and DNA sequence determination of the recombinant phage and comparison to total genomic DNA confirmed that the genes are in tandem, 13.5 kilobase pairs apart, with the albumin gene to the 5' side of the AFP gene. Thus, they are transcribed from the same strand of DNA.